Identification of Student Problems in Class X SMA Negeri 53 Central Maluku - Sawal Mahaly; Emma Rumahlewang (Peneliti.net, 2022)
The complexity of the problems experienced by every human being is different from one another as well as students in schools as individuals can certainly have problems. The problems experienced by students include individual development, individual differences in terms of intelligence, skills, learning outcomes, individual needs in terms of affection, gaining self-esteem, self-adjustment and behavioral disorders as well as learning problems for that teachers need to help students identify problems what is experienced by students at school and outside school. The purpose of this study is to help teachers, especially guidance and counseling teachers, to identify and overcome problems experienced by students. This type of research is a descriptive study with a sample of 30 students of class X SMA Negeri 53 Central Maluku. The method of determining the sample using saturated sampling. Based on the results of the research, the most dominant problems experienced by students were personal problems with a total of 772 problems with an average presentation of 36.76%.